Bradyrhizobium agreste sp. nov., Bradyrhizobium glycinis sp. nov. and Bradyrhizobium diversitatis sp. nov., isolated from a biodiversity hotspot of the genus Glycine in Western Australia. Issue 3 (12th March 2021) - Klepa, Milena Serenato; Ferraz Helene, Luisa Caroline; O'Hara, Graham; Hungria, Mariangela
Abstract : Strains of the genus Bradyrhizobium associated with agronomically important crops such as soybean ( Glycine max ) are increasingly studied; however, information about symbionts of wild Glycine species is scarce. Australia is a genetic centre of wild Glycine species and we performed a polyphasic analysis of three Bradyrhizobium strains—CNPSo 4010 T, CNPSo 4016 T, and CNPSo 4019 T —trapped from Western Australian soils with Glycine clandestina, Glycine tabacina and Glycine max, respectively. The phylogenetic tree of the 16S rRNA gene clustered all strains into the Bradyrhizobium japonicum superclade; strains CNPSo 4010 T and CNPSo 4016 T had Bradyrhizobium yuanmingense CCBAU 10071 T as the closest species, whereas strain CNPSo 4019 T was closer to Bradyrhizobium liaoningense LMG 18230 T . The multilocus sequence analysis (MLSA) with five housekeeping genes— dnaK, glnII, gyrB, recA and rpoB —confirmed the same clusters as the 16S rRNA phylogeny, but indicated low similarity to described species, with nucleotide identities ranging from 93.6 to 97.6% of similarity. Considering the genomes of the three strains, the average nucleotide identity and digital DNA–DNA hybridization values were lower than 94.97 and 59.80 %, respectively, with the closest species. In the nodC phylogeny, strains CNPSo 4010 T and CNPSo 4019 T grouped with Bradyrhizobium zhanjiangense and Bradyrhizobium ganzhouense, respectively, while strain CNPSo 4016 T was positioned separately from the all symbiotic Bradyrhizobium species. Other genomic (BOX-PCR), phenotypic and symbiotic properties were evaluated and corroborated with the description of three new lineages of Bradyrhizobium . We propose the names of Bradyrhizobium agreste sp. nov. for CNPSo 4010 T (=WSM 4802 T =LMG 31645 T ) isolated from Glycine clandestina, Bradyrhizobium glycinis sp. nov. for CNPSo 4016 T (=WSM 4801 T =LMG 31649 T ) isolated from Glycine tabacina and Bradyrhizobium diversitatis sp. nov. for CNPSo 4019 T (=WSM 4799 T =LMG 31650 T ) isolated from G. max .